Tracking chlorinated contaminants in the subsurface using analytical, numerical and geophysical methods - Lin, Fei; Ren, Honglei; Yang, Jie; Li, Yucheng; Kang, Bo; Tao, Yuezan (Frontiers in Environmental Science, 2022)
In recent years, many research methods have been developed for the traceability of groundwater contamination source, in which the numerical simulation and analytical methods are the most common methods to study on groundwater flow and solute transport. However, the establishment and solution of an optimization model is a very complex inverse problem. Given that many decision variables are needed to be identified, two relatively simple analytical and numerical methods are applied for the prediction of chloride migration range and duration process in source area, then the geophysical prospecting and drilling sampling analysis are also used for the verification, moreover, the source center is determined based on the difference between predicted results and measured results. In addition, the influence of the observation points layout, hydrodynamic dispersion parameters and groundwater flow rate on the traceability effect are also analyzed. The results show that located observation points can reflect the chloride distribution accurately, hydrodynamic dispersion parameters and groundwater flow rate have more significant impacts on the traceability effect compared with other factors. Lastly, the proposed model application process is also discussed in the limited scale site, and it provides the reference for source traceability and subsequent remediation design under the similar hydrogeological conditions.